Pengaruh Kondisi Keuangan, Audit Tenure, dan Ukuran KAP terhadap Opini Audit Going Concern pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2016 - Maria Dini Yanuariska; Aloysia Yanti Ardiati (Universitas Proklamasi 45 Yogyakarta, 2018)
Going concern audit opinion is the survival of a company. A company that is considered unable to maintain its survival will receive going concern audit opinion. This opinion is bad news for users of financial statements (Astuti and Darsono, 2012). This research was conducted at manufacturing companies listed in Indonesia Stock Exchange from 2012 until 2016. Based on the criteria of research sample, it was obtained 400 research samples. The purpose of this research was to discover the effect of financial condition, audit tenure, and the size of public accountant office on going concern audit opinion. The results of this study indicated that the financial condition had a positive effect on going concern audit opinion, audit tenure had negative effect on going concern audit opinion, and the size of public accountant office had no effect on going concern audit opinion.